2003
DOI: 10.1021/bi027319b
|View full text |Cite
|
Sign up to set email alerts
|

D18G Transthyretin Is Monomeric, Aggregation Prone, and Not Detectable in Plasma and Cerebrospinal Fluid:  A Prescription for Central Nervous System Amyloidosis?

Abstract: Over 70 transthyretin (TTR) mutations facilitate amyloidosis in tissues other than the central nervous system (CNS). In contrast, the D18G TTR mutation in individuals of Hungarian descent leads to CNS amyloidosis. D18G forms inclusion bodies in Escherichia coli, unlike the other disease-associated TTR variants overexpressed to date. Denaturation and reconstitution of D18G from inclusion bodies afford a folded monomer that is destabilized by 3.1 kcal/mol relative to an engineered monomeric version of WT TTR. Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
128
1
4

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 116 publications
(138 citation statements)
references
References 22 publications
5
128
1
4
Order By: Relevance
“…Four TTR variants were used for the studies presented: WT TTR, the amyloidogenic mutant TTR with Val30Met mutation (V30M TTR), and two engineered variants that do not tetramerize, referred to as monomeric WT (F87M͞ L110M TTR, named WT M-TTR), and monomeric V30M (V30M͞F87M͞L110M TTR, designated V30M M-TTR) TTR. The proteins were prepared and purified in an Escherichia coli expression system as described elsewhere (10)(11)(12). The four protein variants were purified by gel filtration on a Superdex 75 column (Amersham Biosciences) in 10 mM phosphate buffer (sodium) pH 7.6͞100 mM KCl͞1 mM EDTA before each experiment to ensure that no aggregates were present in the starting material.…”
Section: Methodsmentioning
confidence: 99%
“…Four TTR variants were used for the studies presented: WT TTR, the amyloidogenic mutant TTR with Val30Met mutation (V30M TTR), and two engineered variants that do not tetramerize, referred to as monomeric WT (F87M͞ L110M TTR, named WT M-TTR), and monomeric V30M (V30M͞F87M͞L110M TTR, designated V30M M-TTR) TTR. The proteins were prepared and purified in an Escherichia coli expression system as described elsewhere (10)(11)(12). The four protein variants were purified by gel filtration on a Superdex 75 column (Amersham Biosciences) in 10 mM phosphate buffer (sodium) pH 7.6͞100 mM KCl͞1 mM EDTA before each experiment to ensure that no aggregates were present in the starting material.…”
Section: Methodsmentioning
confidence: 99%
“…NIH-PA Author Manuscript NIH-PA Author Manuscript compared and integrated with known dissociation and unfolding rates (7,8,12,13,18,47), in order to gain insight into factors that may lead to amyloid disease. Another advantage of the method is that stability parameters can be derived using only tryptophan fluorescence data.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…A number of autosomal dominant TTR amyloidoses have also been described that are associated with the deposition of variant transthyretin. These disorders have been subcategorized as familial amyloid polyneuropathy (FAP), familial amyloid cardiomyopathy (FAC), or central nervous system selective amyloidosis (CNSA), depending on the tissue(s) affected by deposition of the mutant TTR proteins (8,12,13,28,29).The liver secretes TTR into the blood, whereas the choroid plexus secretes TTR into the CSF -secreted TTR from the liver and the choroid appear to be the source of amyloidogenic transthyretin in the periphery and the brain, respectively. Gene therapy mediated by replacing a disease-associated variant TTR/WT TTR expressing liver by a WT TTR/WT TTR expressing liver through transplantation has proven useful as a strategy for treating familial amyloid polyneuropathy (30).…”
mentioning
confidence: 99%
“…In 1978, Costa et al (18) demonstrated that TTR was the major component of amyloid fibrils associated with familial amyloid polyneuropathy (FAP). Since this discovery, TTR has been implicated as the causative agent in a variety of amyloid diseases [including senile systemic amyloidosis (SSA), familial amyloid cardiomyopathy (FAC), and central nervous system selective amyloidosis (CNSA)], with SSA resulting from the deposition of wild-type TTR (WT-TTR) in the heart and the remaining diseases (FAC, FAP and CNSA) associated with the accumulation of one of Ͼ70 TTR variants in a variety of tissues (19)(20)(21)(22)(23)(24). Currently, the only treatment available for FAP is gene therapy mediated by liver transplantation, in which a liver producing WT-TTR is substituted for the FAP variant-producing organ.…”
mentioning
confidence: 99%